Mutual Influence of Contact Processes in the Simultaneous Interaction of Active and Inert Metal Melts with ZrO2 Ceramics - Durov, O. V.; Stetsyuk, T. V.; Krasovskyy, V. P. (Powder metallurgy and metal ceramics, 2024)
The processes occurring in the simultaneous contact of ZrO 2 ceramics with two metal melts, inert (Cu, Cu–Ga, Ge, Cu–Ge) and active (Cu–Ga–Ti, Cu–Ti), were studied. The experiments were conducted in a high vacuum using thin ZrO 2 ceramic plates, with one side in contact with a droplet of active melt and the opposite side with a droplet of inert melt. In the simultaneous interaction of active and inert metal melts with zirconium dioxide, the interface processes showed mutual influence: oxygen-deficient zirconium dioxide (ZrO 2– x ) was formed through the absorption of oxygen from ZrO 2 by the active melt. This contributed to the dissolution of zirconium from the solid oxide in the inert melt, thereby activating it and increasing its adhesion to the substrate. At the same time, the dissolution of zirconium in the inert melt reduced the oxygen deficiency in zirconium dioxide, i.e., restoring its stoichiometry and promoting further absorption of oxygen by the active melt. Thus, with the simultaneous contact of active and inert melts with ZrO 2 , a larger amount of oxygen dissolves in the active melt, which leads to the saturation of the active melt with oxygen. This results in effects such as the loss of metallic luster and spherical shape of droplets in the active melt, delamination of the active melt, and increase in the thickness of the transition layers at the interface between the active melt and ZrO 2 . The results are significantly influenced by the amounts of inert and active melts in contact with ZrO 2 and by the concentration of the active component (titanium) in the system. The results can be used in the development of methods for brazing and metallization of ceramic materials and techniques for the manufacture and use of refractories and high-temperature electrochemical devices.